Correction: Long-range mechanical signaling in biological systems. Issue 2 (8th December 2020) - Alisafaei, Farid; Chen, Xingyu; Leahy, Thomas; Janmey, Paul A.; Shenoy, Vivek B.
Abstract : Correction for 'Long-range mechanical signaling in biological systems' by Farid Alisafaei et al., Soft Matter, 2020, DOI: ; 10.1039/d0sm01442g .